Pemberdayaan Komunitas Pengungsi melalui Pelatihan Pembuatan Lilin Aromaterapi dan Pengusir Nyamuk Ramah Lingkungan di IOM Sawotratap, Sidoarjo - Frasetya, Rizky Dwi; Wibowo, Adjie Satrio; Moch. Yasin Alfa Dani; M. Sirojul Munir; Petrasia Yao; Ricky Alejandro Martin (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2025)
This community service activity aims to empower the refugee community in IOM Sawotratap, Sidoarjo, through training in making aromatherapy candles and mosquito repellents from natural and environmentally friendly materials. The main problems faced by residents are limited access to formal employment and environmental health risks. The activities were carried out in the form of counseling, demonstrations, and direct practice. The results of the activities showed that participants were able to understand the benefits of aromatherapy and independently produce quality candles. This activity contributed to improving the skills of residents and opening up opportunities for small, home-based businesses.